RHYTHM DISORDERS IN PATIENTS WITH CHRONIC KIDNEY DISEASE RECEIVING HEMODIALYSIS TREATMENT (Modern American Journal of Medical and Health Sciences, 2025)
Cardiovascular diseases are one of the most significant predictors of mortality in patients with end-stage renal disease treated with chronic hemodialysis, and cause at least a third of all hospitalizations [Eisner D. et al., 2001; Johnston N. et al., 2008]. According to the US Renal Disease Registry, the five-year survival rate in the general population of patients on hemodialysis is 33.4% [U. S. Renal Data System, 2009]. More than half of the deaths of patients on renal replacement therapy are due to cardiovascular pathology, the mortality from which in patients on hemodialysis is 30-35 times higher compared to the general population [Zavy A.S. et al., 1998; Herzog S.A., 2003; U.S. Renal Data System, 2009]. A significant proportion of deaths in patients with end-stage renal disease receiving hemodialysis treatment are attributed to those associated with coronary heart disease [Foley R.N. et al., 1998a; Sarnak M.J. et al., 2003; Cheung A.K. et al., 2004]. The theoretical method of research was used. Many articles and dissertations by international scientists were analyzed, which were based on various books, dissertations, as well as electronic journals.